Hyaluronic Acid Interactions with Pork Myofibrillar Proteins in Emulsion Gel-Type Systems - Marzena Zając; Lei Zhou; Magdalena Mika; Ziyi Yang; Jingyu Wang; Ye Tao; Wangang Zhang (Molecules)
Health benefits associated with hyaluronic acid, along with its properties such as water-binding capacity and antimicrobial activity, suggest that incorporating it into meat systems could provide a basis for formulating functional meat products. This study aimed to evaluate the properties of myofibrillar protein gels and emulsions with varying concentrations of hyaluronic acid. The results indicate that increasing the hyaluronic acid concentration (0.008% to 0.04%) does not significantly affect the cooking loss, while a concentration of 0.08% enhances cooking loss. This, in turn, increased gel hardness, while the water-holding capacity remains unaffected. Cryo-scanning electron microscopy (Cryo-SEM) images revealed a partial disruption of the gel structure, with rising hyaluronic concentrations. In pork myofibrillar protein emulsions, smaller droplets and higher stability were observed after HA incorporation. Samples containing hyaluronic acid were more viscous and exhibited shear-thinning properties. Overall, the hyaluronic acid used in this study improved emulsion properties, whereas the gel structure was compromised.